(untitled) (Research, Society and Development, 2021)
Language development depends on the interaction of biological, environmental and psychosocial factors existing in the different contexts in which children are inserted. Objective: To evaluate the association of paternal abandonment and socioeconomic factors on the language development of children in a public day care center in the city of Marabá (PA). Method: This is a study of character transverse, carried out with 62 children from 3 to 6 years old. The instruments used were the Poverty Level Measurement Instrument and the Denver II Developmental Screening Test. Statistical analysis the ram used are the tests are Qui-quadrado, Test G and Test U, all with a significance level of 5%. Results: As for the level of poverty, 55 (88.70%) children had a higher low income and 13 (20.97%) children had suspected language delay. Twenty-five (89.30%) children, whose parents worked per job, had questionable outcome. And, 11 (39.30%) children who have been abandoned entirely by s father s had questionable results in the language. Conclusion: Social variables such as paternal abandonment and socioeconomic factors have a direct influence on child language development.